Vipassana Meditation Technique by Satya Narayan Goenka at Dhamma Java Bogor - Eko Susiono; I Wayan Suka Yasa; Ida Ayu Komang Arniati (Sahabat Publikasi, 2026)
In the modern era, many individuals experience spiritual emptiness and mental health disorders due to the pressures of life and loss of meaning in life. S.N. Goenka's technique of Vipassana meditation is present as an alternative to spiritual practice that emphasizes the observation of bodily sensations without ritual and is non-sectarian, thus attracting the interest of lay practitioners from various backgrounds.This research examines one of the rapidly growing practices in Indonesia today: the vipassana meditation technique used by S.N. Goenka. This technique is unique and interesting to study in depth because it uses direct observation of bodily sensations, without rituals, without note-taking, and without jhana requirements, thus attracting modern lay practitioners. This study integrates the reasons why vipassana meditation has not been beneficial for physical and mental health. Based on holistic theory, yoga sutra theory, and Buddhist meditation, it compares, aligns, and analyzes SN Goenka's Vipassana Meditation technique. This study uses data collection techniques including participant observation, direct interviews, and document studies. Data analysis is carried out through data reduction, presentation, and conclusion drawing. Based on data analysis, the following findings were obtained: Holistically, physical and mental causes are not obstacles but rather means to realize bodily sensations, not absolute causes. In sutra yoga theory, sila is in harmony with yama and niyama, emphasizing internal self-discipline. In conclusion, S.N. Goenka's Vipassana meditation technique is a spiritual path to self-transformation that is relevant to physical and mental health today.